Tinjauan Yuridis Terhadap Keterbukaan Pemilik Manfaat Dalam Perseroan Terbatas Berdasarkan Peraturan Presiden Nomor 13 Tahun 2018 - Amanda Serena; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2019)
Abtract. A beneficial owner is an individual who can be said to be a beneficial owner if he/she has income and / or profits due to the ownership of shareholding, capital, initial assets, sources of funding, or other rights that may result in profits from a limited liability company.Individuals who do not have assets in a corporation can also be categorized as a beneficial owner if they have unlimited authority related to the appointment of administratorin a limited liability company management and the control of limited liability company, or are the true owners of the funds for the limited liability company ownership.Furthermore, the existence of beneficial ownership in a limited liability company must be reported to the government.This is done by providing information about beneficial ownership which is certainly can not be separated from the disclosure principles. The limited liability company is often used by villains to hide and obscure the criminal proceeds of crime, money laundering and financing of terrorism through capital participation in the limited liability company by using nominee and becoming beneficial owner.The Government through Presidential Regulation No. 13/ 2018 obliges the beneficial owner of the company (beneficial ownership) to disclose their identity clearly and transparently.This is an effort to supervise and prevent irregularities of the company owner. Furthermore, supervision of disclosure of the limited liability company is carried out by an authorized institution based on the results of the criminal risk assessment of money laundering and terrorism financing. Therefore, the limited liability company that does not specify a beneficial owner and does not submit true information about the beneficial owner in a limited liability company for the authorized institution will be sanctioned in accordance with Presidential Regulation No. 13/ 2018 and with various cross-sectoral regulations related to the limited liability company. Keywords: disclosure, beneficial owner, limited liability company